The Machine as Art/ The Machine as Artist (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The articles collected in this volume from the two companion Arts Special Issues, "The Machine as Art (in the 20th Century)" and "The Machine as Artist (in the 21st Century)", represent a unique scholarly resource: analyses by artists, scientists, and engineers, as well as art historians, covering not only the current (and astounding) rapprochement between art and technology but also the vital post-World War II period that has led up to it; this collection is also distinguished by several of the contributors being prominent individuals within their own fields, or as artists who have actually participated in the still unfolding events with which it is concerned